2022
DOI: 10.1021/acs.macromol.2c01682
|View full text |Cite
|
Sign up to set email alerts
|

Radical Oxidation of Itaconic Acid-Derived Unsaturated Polyesters under Thermal Curing Conditions

Abstract: Itaconic acid has attracted a lot of interest as a green and low-cost building block toward the synthesis of biobased polyesters and polyurethanes with a wide range of applications in the UV-curing field. However, the thermal curing of itaconic acid-derived polyesters has been not extensively investigated. To gain deeper insight into the thermally induced crosslinking process, the curing of poly­(hexylene itaconate) was investigated by advanced isoconversional analysis performed under isothermal and non-isothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The results of these calculations provide E α as a function of the extent of conversion α, without necessitating assumptions about the underlying reaction mechanism. These E α dependencies have been demonstrated to enable meaningful mechanistic analyses and enhance our comprehension of multi-step processes. ,, …”
Section: Methodsmentioning
confidence: 99%
“…The results of these calculations provide E α as a function of the extent of conversion α, without necessitating assumptions about the underlying reaction mechanism. These E α dependencies have been demonstrated to enable meaningful mechanistic analyses and enhance our comprehension of multi-step processes. ,, …”
Section: Methodsmentioning
confidence: 99%
“…More specifically, over 80 ktons/a is produced via sugar fermentation by the fungus Aspergillus terreus and the price is less than 2 €/kg. In addition, itaconic acid has the advantage to be very versatilely applicable. First, it is considered as an alternative to maleic acid in bio-based unsaturated polyester resins for thermosetting applications. In this respect, recent studies have shown that the utilization of itaconic acid in these applications results in the reduction of greenhouse gas emissions and of the total energy consumption . Second, the external double bond exhibits a higher reactivity toward radical reactions compared to the internal double bond of the maleic acid.…”
Section: Introductionmentioning
confidence: 99%
“…First, it is considered as an alternative to maleic acid in bio-based unsaturated polyester resins for thermosetting applications. 8 13 In this respect, recent studies have shown that the utilization of itaconic acid in these applications results in the reduction of greenhouse gas emissions and of the total energy consumption. 14 Second, the external double bond exhibits a higher reactivity toward radical reactions compared to the internal double bond of the maleic acid.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, biomass-sourced molecules derived from various raw materials possess well-defined functionality and accurate molecular structures . Itaconic acid as one of the top 12 biomass-derived molecules provides a renewable feedstock alternative for fabricating polymer materials. …”
Section: Introductionmentioning
confidence: 99%